Young urban Shona women and men negotiating gender and sexuality and social identifications through “cultural practices” in contemporary Zimbabwe: the case of labia elongation. - Venganai, Helen (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.